2015
DOI: 10.1017/s2045796015000748
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and acceptability of psychological interventions for depression: where we are now and where we are going

Abstract: Depression is an eminently treatable disorder, although estimates of treatment efficacy have been inflated by publication bias. Patients with less severe depressions respond to even nonspecific interventions, whereas patients with more severe depressions require treatments that mobilize specific mechanisms. The cognitive and behavior therapies can be as efficacious as medications in the treatment of severe depression and have an enduring effect that medications lack. Medications may interfere with those enduri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Put another way, controlling for depressive symptoms that are concurrent with AD use may cause researchers to underestimate the adverse health effects of AD use. One possible explanation is that AD use only leads to a transient reduction in depressive symptoms because they induce an oppositional tolerance (caused by mechanisms in the brain responsible for maintaining homeostasis) that interferes with spontaneous remission and prolongs episodes [19,27,94,95,96]. Under this hypothesis, depressive symptoms under prolonged AD use (i.e., months or longer) are higher than they would be without medication, and partialling out concurrent depression also partials out the negative health effects of ADs that covary with this iatrogenic depression.…”
Section: Discussionmentioning
confidence: 99%
“…Put another way, controlling for depressive symptoms that are concurrent with AD use may cause researchers to underestimate the adverse health effects of AD use. One possible explanation is that AD use only leads to a transient reduction in depressive symptoms because they induce an oppositional tolerance (caused by mechanisms in the brain responsible for maintaining homeostasis) that interferes with spontaneous remission and prolongs episodes [19,27,94,95,96]. Under this hypothesis, depressive symptoms under prolonged AD use (i.e., months or longer) are higher than they would be without medication, and partialling out concurrent depression also partials out the negative health effects of ADs that covary with this iatrogenic depression.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of ADMs are particularly robust for individuals with severe depression (see Hollon, 2016 for a review). ADMs are the most common treatment for depression in child-bearing age women (Ko, Farr, Dietz, & Robbins, 2012).…”
Section: Depression In Mothers and Children’s Adjustmentmentioning
confidence: 99%
“…Importantly, CBT has enduring effects that last beyond the end of the acute treatment, and are about the same as remaining on ADMs. CBT also is about two and a half times more likely to prevent recurrence as compared to stopping ADMs (see Hollon, 2016 for a review). With regard to perinatal depression in particular, a meta-analytic review (Sockol, 2015) showed that interventions based on CBT resulted in significant reductions in depressive symptoms compared to controls, with even greater reductions in depression in studies that included higher proportions of mothers who were nonwhite, single, and had more than one child.…”
Section: Depression In Mothers and Children’s Adjustmentmentioning
confidence: 99%
“…Adequate implementation of protocolized, evidence-based psychotherapy such as cognitive behavioral therapy (CBT) and interpersonal psychotherapy (IPT) has been associated with better treatment outcomes [ 1 , 2 ]. Unfortunately, a large number of patients still receives inadequate or suboptimal psychological treatment [ 3 9 ].…”
Section: Introductionmentioning
confidence: 99%